Integration of Language Skills in Czech Language Testing - Pechova, Vladimira (Bohemica Olomucensia, 2023)
The integration of language skills as an integral part of the everyday communication is reflected in modern methods of teaching second language. However, many high-stakes language exams still assess language skills separately. To reflect modern trends, an integrated listening-to-writing task was included in the end-of-course exams of Czech at the Institute of Language and Preparatory Studies, Charles University in Prague. Passing this exam and getting a certificate of language proficiency allow students to apply for Czech public universities and study in Czech. In this paper the content, construct and decision to include integrated task in the exam will be discussed from an experience based perspective.
Keywords: Czech Language Exams; Integration of Language Skills; Integrated Task; Listening-to-Writing Task; Level B1 and B2 of the CEFR; Rating Criteria